Assessment of trace metal contamination and its anthropogenic influence in the sediments of an urban water body in Kozhikode, Kerala, India. Issue 4 (2nd October 2018) - Siddik, A. Muhammed; Chand, Aswin; Varghese, George K.; Alappat, Babu J.
Abstract: Urban water bodies in India receive pollution loads from numerous sources. Identification of the polluter in such cases is a difficult process. An investigation of forensic nature is needed for this. The present study targets the Conolly canal (aka Canolly Canal in local parlance) passing through the centre of Kozhikode city, constructed for inland navigation during the British reign of India. It is a typical urban water body that is exposed to different point and non-point sources of pollution, directly receiving untreated municipal and industrial sewage, in addition to storm water. For the identification of the sources polluting the Canal, an investigation following the guidelines regarding the collection of samples in the 'Pollution Crime Forensic Investigation Manual' published by the INTERPOL, was carried out. The human influence on the heavy metals (Cd, Cr, Cu, Hg, Fe and Pb) concentration in the canal sediments was analysed using the following indices – Enrichment factor (EF), contamination factor (CF) and geo-accumulation index (Igeo ). Sediment samples for the study were collected from the different locations and depths of the canal bed and were analysed using atomic absorption spectrometry. All the three indices showed human influence on the heavy metals contamination of the canal. The results indicated that the EF and CF for the metals analysed are in the order of Cd > Cu > Cr > Hg > Pb. The Igeo showed high pollution level for the metals Cd and Cr. All three indices showed maximum values for the top (surface) sediments, which indicated the ongoing waste disposal into the canal. The study also revealed that the contamination levels are very high at the location where a major drain discharges waste water into the canal and the level of contamination was above the limiting value set by the World Health Organisation, and hence a cause for serious concern.